MEASURES IMPLEMENTED IN THE INDUSTRY OF THE SURKHANDARYA OASIS AND THEIR CONTRIBUTION TO THE DEVELOPMENT OF THE INDUSTRY (IN THE YEARS OF INDEPENDENCE) (American Journal of Business Management, Economics and Banking, 2023)
The purpose of this article is to scientifically and historically illuminate the essence of the policy of the government of the Republic of Uzbekistan aimed at establishing world-class industrial enterprises in the Surkhandarya oasis during the years of independence.